1996
DOI: 10.1146/annurev.arplant.47.1.273
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHOENOLPYRUVATE CARBOXYLASE: A Ubiquitous, Highly Regulated Enzyme in Plants

Abstract: Since plant phosphoenolpyruvate carboxylase (PEPC) was last reviewed in the Annual Review of Plant Physiology over a decade ago (O'Leary 1982), significant advances have been made in our knowledge of this oligomeric, cytosolic enzyme. This review highlights this exciting progress in plant PEPC research by focusing on the three major areas of recent investigation: the enzymology of the protein; its posttranslational regulation by reversible protein phosphorylation and opposing metabolite effectors; and the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
567
0
13

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 650 publications
(605 citation statements)
references
References 136 publications
(204 reference statements)
25
567
0
13
Order By: Relevance
“…A number of studies thus far have shown that CAM-specific PEPC1 transcripts in a 553 facultative CAM plant show higher abundance at night (Cushman et al, 2008), whereas in C 3 554 and C 4 plants, these transcripts are more abundant during the day (Chollet et al, 1996). Previous 555 findings suggest that the PEPC activity is increased at night; however, its protein abundance 556 pattern varies over the diel cycle in facultative CAM species (Häusler et al, 2000).…”
Section: Cam In Agave 552mentioning
confidence: 99%
“…A number of studies thus far have shown that CAM-specific PEPC1 transcripts in a 553 facultative CAM plant show higher abundance at night (Cushman et al, 2008), whereas in C 3 554 and C 4 plants, these transcripts are more abundant during the day (Chollet et al, 1996). Previous 555 findings suggest that the PEPC activity is increased at night; however, its protein abundance 556 pattern varies over the diel cycle in facultative CAM species (Häusler et al, 2000).…”
Section: Cam In Agave 552mentioning
confidence: 99%
“…PEPC is a highly regulated enzyme that is allosterically activated by Glc-6-P and triose-P and inhibited by L-malate and Asp (Schuller et al, 1990). Furthermore, the sensitivity of the protein to allosteric regulation is modified by its phosphorylation state (Chollet et al, 1996). When phosphorylated, the protein is less sensitive to allosteric regulation.…”
Section: Is Cellular Metabolism Specialized During Cluster-root Carbomentioning
confidence: 99%
“…Nitrate assimilation and organic acid metabolism also respond to changes of cellular pH. Alkalization leads to post-translational inhibition of NIA (Kaiser & BrendleBehnisch 1995;Botrel & Kaiser 1997), and activates PEPC by decreasing sensitivity to feedback inhibition by malate (Chollet, Vidal & O'Leary 1996;Nimmo 2000).…”
Section: Introductionmentioning
confidence: 99%